PENGEMBANGAN MEDIA GAMBAR KOMIK CERITA RAKYAT “BARU KLINTHING’’ DALAM MENANAMKAN LITERASI BUDAYA SISWA KELAS I SDN KLEPU 01 KABUPATEN SEMARANG - yovita rahmadya rehandini; Wakhyudin, Husni; Ikha Listyarini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low interest of elementary school students in cultural literacy learning due to the limited availability of interesting learning media. At SDN Klepu 01, teachers still rely on long textbooks that are less suited to student characteristics. This research aims to develop the “Baru Klinthing” folklore comic media as an innovative means to instill cultural literacy in first grade students. The method used is Research and Development with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of material experts, media experts, first grade teachers, and 28 students of SDN Klepu 01. Data were collected through validation sheets, questionnaires, and field trials, then analyzed descriptively quantitatively and qualitatively. The results showed that the comic media obtained validation from material experts of 97.5% and media experts of 92.5% (both very valid). Teacher responses reached 100% (very good) and students 91.43% (practical). Comics were considered interesting, easy to use, and effective in helping the understanding of cultural values. Thus, the comic media "Baru Klinthing" is declared valid, appropriate, and well-received by teachers and students, and is effective in increasing reading interest and cultural literacy of elementary school students.